Characterizing the HIV Epidemic in the Prairie Provinces. Issue 1 (2012) - Becker, Marissa L; Kasper, Ken; Pindera, Carla; Cheang, Mary; Rodger, Debbie; Sanche, Stephen; Skinner, Stuart; Gill, M John
Abstract : BACKGROUND: The numbers and demographics of HIV-positive patients in care between 2003 and 2007 in the prairie provinces were examined. METHODS: Estimates of HIV-positive patients presenting to care between 2003 and 2007 were obtained from four clinic registries in Manitoba, Saskatchewan and southern Alberta. Detailed data were collected from clinical records of new patients in 2007. RESULTS: By the end of December 2007, 2263 HIV-positive persons were in care in Manitoba, Saskatchewan and southern Alberta. Males and females accounted for 1674 (74.0%) and 589 of the cases, respectively. Overall, there was a 12% increase per year in new HIV cases to care between 2003 and 2007 (P=0.026), with the rate of increase for males being 60% higher than for females over this time period (P=0.002). In 2007, there were 222 new HIV cases to care (37.4% female). Heterosexual contact was the most common HIV risk, but diversity was seen across sites with frequent injection drug use and men who have sex with men risk in Saskatchewan and southern Alberta, respectively. The Aboriginal population remains heavily over-represented, with approximately 36.0% of new cases being Aboriginal. Late presentation was common across all care sites, with 35.1% of cases presenting with CD4 counts of less than 200 cells/mm 3 . DISCUSSION: Heterosexual risk is the most common risk reported for HIV acquisition, but injection drug use risk remains significant in Saskatchewan. Aboriginals are over-represented at all sites, and in Saskatchewan accounted for the majority of new cases seen. In contrast to national trends, numbers of new and late diagnoses are increasing in the praire provinces, and this has significant treatment implications and potential public health consequences. Further efforts need to be made to facilitate earlier testing and linkage to care.